PENGARUH SALINITAS TERHADAP SERANGAN PENGGEREK KAYU DI LAUT PADA BEBERAPA JENIS KAYU - Mohammad Muslich; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Marine borers are wood destroying organisms living in the sea, brackish and estuarine water. Environmental conditions such as salinity, pollution and temperature of the sea water influence the activities and precence of marine borers.One hundred pieces of wood from five species had been exposed to marine borers in four different salinities for nine months. The test sites chosen were around Gulf of Jakarta i.e. about 3 km off shore, and at three locations along a canal of brackish fishpond, respectively in the estuary, 1 km and 2 km from the shore.The result shows that at the sea site where the salinity is relatively stable around 29 ‰ – 30‰ , all of the wood tested are badly attacked by Mollusc belonging to the species of Martesia striata Linne., Dicyathifer manni Wright., and Bankia campanellata Moll/Roch. Along the canal where the salinity is between 5‰-30‰, damage is only small. The result also shows no sign of attack on all samples exposed along the canals, although the salinity is not significantly different from that of the estuary.